Geometry-symmetry-free and material-symmetry-guaranteed polariton-induced transparency - Xingyu Tang; Huaping Wang; Zhenyang Cui; Sihao Xia; Zhiwei He; Song Han; Hongsheng Chen; Yingjie Wu (iScience)
Summary: Plasmon-induced transparency is a classical analogue of electromagnetically induced transparency (EIT). However, its realization and control primarily rely on geometry engineering rather than tuning plasmon polaritons (PPs) themselves, due to their relatively poor tunability. Recently discovered polariton modes in low-symmetry materials exhibit volume-confined field distributions, thickness-dependent dispersions, and in-plane anisotropy, offering possibilities for the realization and manipulation of polariton-induced transparency (PIT). In this study, we theoretically achieve geometry-symmetry-free and material-symmetry-guaranteed PIT based on volume-confined phonon polaritons (vPhPs) in stacked bilayer α-MoO3 structures. PIT arises from the strong resonance of vPhPs and the subsequent robust near-field coupling at large thicknesses, where the in-plane anisotropy of vPhPs results in multi-spectral PIT across different polariton bands, enabling the tuning of PIT by adjusting the lattice orientation of α-MoO3 without altering geometry. These findings highlight the potential of polariton modes beyond PPs in PIT systems, with applications in sensors, modulators, and slow light systems.